Cathelicidins enhance protection of channel catfish, Ictalurus punctatus, and channel catfish ♀ × blue catfish, Ictalurus furcatus ♂ hybrid catfish against Edwarsiella ictaluri infection. Issue 12 (15th September 2020) - Simora, Rhoda Mae C.; Li, Shangjia; Abass, Nermeen Y.; Terhune, Jeffery S.; Dunham, Rex A.
Abstract: Cathelicidins are a class of antimicrobial peptides (AMPs) known to possess rapid and direct antimicrobial activities against a variety of microorganisms. Recently identified cathelicidins derived from alligator and sea snake were found to be more effective in inhibiting microbial growth than other AMPs previously characterized. The ability of these two cathelicidins along with the peptides, cecropin and pleurocidin, to protect channel catfish ( Ictalurus punctatus, Rafinesque) and hybrid catfish ( I. punctatus ♀ × blue catfish, Ictalurus furcatus, Valenciennes ♂ ) against Edwardsiella ictaluri, one of the most prevalent pathogens affecting commercial catfish industry, was investigated. Cathelicidin‐injected fish (50 µg ml −1 fish −1 ) that were simultaneously challenged with E. ictaluri through bath immersion at a concentration of 1 × 10 6 CFU/ml had increased survival rates compared with other peptide treatments and the infected control. Bacterial numbers were also reduced in the liver and kidney of channel catfish and hybrid catfish in the cathelicidin treatments 24 hr post‐infection. After 8 days of challenge, serum was collected to determine immune‐related parameters such as bactericidal activity, lysozyme, serum protein, albumin and globulin. These immune‐related parameters were significantly elevated in fish injected with the two cathelicidins as compared to other peptide treatments. These results indicate that cathelicidins derived from alligator and sea snake can stimulate immunity and enhance the resistance to E. ictaluri infection in channel catfish and hybrid catfish.